What Is Scrumban? - Stellman, Andrew (O'Reilly Media, Inc., 2019)
The most common Agile framework for project management and product delivery today is Scrum. If you combine Scrum with Kanban-an Agile method for process improvement and workflow management-you get Scrumban: a project management/product delivery tool that features pull systems, workflow visualization, and process improvement. In this report, Andrew Stellman examines the fundamentals of Scrum and Kanban, and explains how a Scrumban hybrid can combine Scrum and Kanban effectively and take both of them to the next level. A widely recognized expert in transforming and improving software organizations, teams, and code, Stellman explains how teams that adopt Scrumban combine the core parts of both approaches to deliver better products today while continuing to improve into the future. Agile practitioners will discover why a growing number of software teams now use Scrumban. Review the core elements of Scrum and Kanban for product delivery and process improvement Understand how Scrumban incorporates the empirical process control of Scrum with the pull systems of Kanban to maintain the integrity of both Explore common misconceptions, including the notion that Scrum and Kanban have the same goals or that Scrumban is just "iterationless" Scrum Learn how to use your current Scrum implementation as a starting point for meaningful process improvement that can make your product delivery even more effective Examine a case study that describes a successful real-world implementation of a Scrum and Kanban hybrid